Perspective of application of nonlinear stimulation therapy in the treatment of traumatic brain injuries and maintenance of cognitive functions in the elderly - M. V. Zueva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Cognitive decline characterizes normal physiological aging and is aggravated by the development of age-related neurodegenerative pathology and traumatic brain damage (TBI). Te review analyzes widely discussed in the scientifc literature non-drug methods of rehabilitation of patients with TBI and elderly people suﬀering from cognitive decline, including the paradigm of enrichment of the environment, cognitive and physical training and various types of stimulation therapy and their shortcomings. Special attention is paid to the advantages of fractal stimulation of the brain by complex-structured optical signals and sensory stimuli of another modality. It is assumed that the use of new approaches to neurorehabilitation, which increase the potential of neuroplasticity will also allow strengthening the therapeutic and learning impacts of any other methods of training and treating the brain.